High Levels of Perfluorooctane Sulfonate in Children at the Onset of Diabetes. (5th May 2015) - Predieri, Barbara; Iughetti, Lorenzo; Guerranti, Cristiana; Bruzzi, Patrizia; Perra, Guido; Focardi, Silvano E.
Abstract : Background . Impairments of endocrine system may be associated with exposure to perfluorinated compounds that are able to bind nuclear receptors, including the peroxisome proliferator-activating receptors. Aim of this study was to assess perfluorooctane sulfonate and perfluorooctanoic acid concentrations in children and adolescents at the onset of type 1 diabetes compared to healthy controls. Methods . Forty-four children and adolescents were recruited and subdivided into two groups: (A) 25 subjects with type 1 diabetes and (B) 19 healthy controls. Perfluorinated compounds were measured using high performance liquid chromatography with electrospray ionization tandem mass spectrometry. Nonparametric statistical analysis was performed. Results . Perfluorooctane sulfonate concentrations were significantly higher in patients with type 1 diabetes compared to controls (1.53 ± 1.50 versus 0.55 ± 0.15 ng/mL, resp.;p < 0 . 001 ). Multivariate linear regression analysis identified lipid levels as significant predictive factors for perfluorooctane sulfonate levels. Conclusions . Our data suggests that higher serum levels of perfluorooctane sulfonate may be considered a biomarker of exposure and susceptibility to develop type 1 diabetes.